The potential of chimeric antigen receptor -T cell therapy for endocrine cancer - Ruonan Yu; Xiaoyu Ji; Ping Zhang; Hao Zhang; Huiling Qu; Wenwu Dong (World Journal of Surgical Oncology)
Abstract Endocrine cancer, a relatively rare and heterogeneous tumor with diverse clinical features. The facile synthesis of hormones further complicates endocrine cancer treatment. Thus, the development of safe and effective systemic treatment approaches, such as chimeric antigen receptor (CAR) T cell therapy, is imperative to enhance the prognosis of patients with endocrine cancer. Although this therapy has achieved good results in the treatment of hematological malignancies, it encounters diverse complications and challenges in the context of endocrine cancer. This review delineates the generation of CAR-T cells, examines the potential of CAR-T cell therapy for endocrine cancer, enumerates pivotal antigens linked to endocrine cancer, encapsulates the challenges confronted with CAR-T cell therapy for endocrine cancer, and expounds upon strategies to overcome these limitations. The primary objective is to provide insightful perspectives that can contribute to the advancement of CAR-T cell therapy in the field of endocrine cancer.